Azerbaijan Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper and Statistical Appendix for Azerbaijan aims to provide a guide to the management of Azerbaijan's expected natural resource-generated windfall. The paper provides information on Azerbaijan's endowment of oil and gas deposits and the projected revenue stream, and highlights the common characteristics of policies leading to the mismanagement of natural resource wealth in natural resource-abundant countries. It also outlines a medium- and long-term policy strategy for oil wealth management in Azerbaijan.